The Significance of Green Infrastructure Experience to Cognitive Well-Being of Residents in Small Town - Mansor, Mazlina; Said , Ismail; Labintah, Suraidah (2009)
The paper explored the significance of residents’ experience with an array of green infrastructure in Taiping, a small town in central Peninsular Malaysia. It argued that the existence of a composite of greenery and open spaces in a town with pleasing qualities contributes to cognitive performance, through contact and participation. In particular, it examined the relationship of participation in the green spaces to residents’ cognitive well-being. Green infrastructure network is greenery and open spaces linked by walkways, streets, waterways and drainage ways around and between urban areas, at all spatial scales. In Taiping, the green infrastructure network consists of the Lake Gardens (town park), river corridors, street plantings, school playfields, neighbourhood open spaces, home gardens and loose-fit spaces such as pocket spaces in between buildings and shop-houses. Ease of access to green infrastructure network, physically and visually facilitates residents to participate in active activities, to socialize and to perform other transactional activities outside their homes. Therefore, the effects from the participation trigger many positive moods such as serenity, cheerfulness, relaxation, calmness, comfort and satisfaction. Questionnaires (n=335) were used to explore frequency of residents’ visits to the green infrastructure and the causal relationship to cognitive performances that lead to their well-being. The data showed, regardless of ages, residents frequently visited the green spaces. Results also suggested that there was a modest relationship between frequent visits and cognitive wellbeing of residents. Hence, they implied the benefits of access to green spaces and implicated that the existence of green infrastructure network such as parks and neighbourhood open spaces are essential land use in an urban fabric that foster sense of well-being to its inhabitants.